Variables Influencing the Case Prioritisation of Men Convicted of Internet Child Abuse Material Offences - Catherine Garrington; Hannah Merdian; Douglas P. Boer (Sexual Offending, 2020)
The differentiation between men convicted of child abuse material offences, known as Internet Child Abuse Material (I/CAM), and Contact (CO) child sex offenders is an ongoing area of research. Current research indicates there are differences between men convicted of I/CAM and CO offences. This article highlights key variables that may indicate clinically and/or statistically significant differences between I/CAM and CO populations, as identified in current published research. Identified key variables may contribute to the case prioritisation of men under investigation for I/CAM offences to assist timely investigation. Post conviction, key variables may contribute to targeted treatment, reducing recidivism and protecting the global community. Articles containing variables differentiating I/CAM and CO populations were reviewed; articles that did not include any comparative analysis were excluded. The final sample of articles (n = 10) was reviewed using a literature review methodology to collate trend variables and directionality between the two populations. Demographic variables with critical differences between men convicted of I/CAM offences when compared to CO offences are younger age, White ethnic background, employed, lower use of alcohol and drugs, and less or no recorded criminal history but higher self-reported history of offending. Key psychological variables identified are lower impression management, lower demonstrations of antisociality, higher sexual deviancy and higher levels of victim empathy when compared to men convicted of CO offences. The findings will be considered in line with existing risk assessment and case prioritisation tools. This research can contribute to community safety through a specific focus on prioritising the investigation, case management, and treatment of men convicted of I/CAM offences and signals future pathways for targeted risk assessment.